2019
DOI: 10.3389/fped.2019.00296
|View full text |Cite
|
Sign up to set email alerts
|

When Less or More Isn't Enough: Renal Maldevelopment Arising From Disequilibrium in the Renin-Angiotensin System

Abstract: Environmental and nutritional factors during fetal and neonatal life can have long-lasting effects on renal functions and physiology and susceptibility to kidney disease in adulthood. All components of the renin-angiotensin system (RAS) are highly expressed in the kidneys during the period of renal development. The RAS plays a central role in the regulation of various cellular growth factors and stimulates adhesion molecules and cellular migration. The use of antagonists of this system during fetal development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 97 publications
0
4
0
4
Order By: Relevance
“…Vitamin D inhibits renin expression and in turn reduces Ang II expression, thus, serving as a negative RAS regulator [29,30]. The deficiency of vitamin D activates the intrarenal RAS, thereby inducing an increase in the level of Ang II, which is an important stimulator of kidney injury [31,32]. Our study demonstrated that active vitamin D analogs paricalcitol and doxercalciferol were able to suppress RAS activation, alleviate glomerular and tubulointerstitial damage, and reduce proteinuria in streptozotocin (STZ, 40 mg/kg)-induced diabetic DBA/2 J mice [33,34].…”
Section: Renin-angiotensin System (Ras)mentioning
confidence: 99%
“…Vitamin D inhibits renin expression and in turn reduces Ang II expression, thus, serving as a negative RAS regulator [29,30]. The deficiency of vitamin D activates the intrarenal RAS, thereby inducing an increase in the level of Ang II, which is an important stimulator of kidney injury [31,32]. Our study demonstrated that active vitamin D analogs paricalcitol and doxercalciferol were able to suppress RAS activation, alleviate glomerular and tubulointerstitial damage, and reduce proteinuria in streptozotocin (STZ, 40 mg/kg)-induced diabetic DBA/2 J mice [33,34].…”
Section: Renin-angiotensin System (Ras)mentioning
confidence: 99%
“…Vit.D has pleiotropic effects that extend beyond its traditional role in calcium homeostasis [10]. More than 200 genes with Vit.D receptor response elements (VDREs) directly or indirectly influence cell cycling, proliferation, differentiation, and apoptosis and regulation of the renin gene, which are important aspects of development [11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Uma cascata de eventos durante o desenvolvimento renal é rigidamente regulada pelos receptores de ANGII, que são altamente expressos nos rins durante este período (Millan et al, 1989). Assim, a integridade do SRA desempenha um papel fundamental na saúde fetal (Almeida & Coimbra, 2019). O desenvolvimento do rim é um processo altamente complexo que exige uma regulação precisa da proliferação , diferenciação e apoptose celular (Almeida & Coimbra, 2019;Moore et al, 2020).…”
Section: Sistema Renina-angiotensina No Desenvolvimento Renalunclassified
“…Assim, a integridade do SRA desempenha um papel fundamental na saúde fetal (Almeida & Coimbra, 2019). O desenvolvimento do rim é um processo altamente complexo que exige uma regulação precisa da proliferação , diferenciação e apoptose celular (Almeida & Coimbra, 2019;Moore et al, 2020). A distribuição temporal e espacial dos receptores de ANGII do tipo 1 e 2 e seus RNAm durante o desenvolvimento renal tem sido estudado (Gao et al, 2005;Norwood et al, 1997;Kakuchi et al, 1995).…”
Section: Sistema Renina-angiotensina No Desenvolvimento Renalunclassified
See 1 more Smart Citation